Second Level Coping Mechanism: A Study on Problem Solving Measures Taken by Street-Level Bureaucrats Concerning Agrarian Policy in Cipari, Cilacap - Deden Dani Saleh; Wahyudi Kumorotomo; Agustinus Subarsono; Bambang Hudayana (Policy & Governance Review, 2019)
This article concerns the efforts carried out by lower level bureaucrats in order to implement their decisions. Prior studies generally describe the decision of street-level bureaucrats (SLBs) as decisions that have already been implemented. There have not been many studies describing the efforts of SLBs in realizing their decisions. Thus, this study intends to examine the efforts undertaken by the lowest level bureaucrats to implement the decisions they have made. The main reference used to analyze this phenomenon is by using the structural approach and the DNA of negotiation. To describe this phenomenon, the study explored a case of program implementation on land redistribution in the Cipari District, Cilacap Regency in 2010. Study results show that power, strategy, and distributive negotiation tactic, as well as personal values are key elements in implementing decisions. The results indicate that discretion is not always applicable since there are times when discretion is limited and thus it must be developed. Because this study relates to the success or failure of policy implementation, knowledge about ways of developing discretion becomes a substantial part in optimally developing public policy.